Off with their heads! : fairy tales and the culture of childhood - Tatar, Maria, 1945- (Princeton University Press, 1992)
When fairy tales moved from workrooms, taverns, and the fireside into the nursery, they not only lost much of their irreverent, earthy humor but were also deprived of their contestatory stance to official culture. Children's literature, Maria Tatar maintains, has always been more intent on producing docile minds than playful bodies. From its inception, it has openly endorsed a productive discipline that condemns idleness and disobedience along with most forms of social resistance. In this book she explores how Perrault, the Grimms, and others reshaped fairy tales to produce conciliatory literary texts that dedicate themselves to the project of socializing the child. Tatar finds that when we read and interpret fairy tales today, we often fall into the trap of positioning children as the real villains of the tales. Authorities such as Bruno Bettelheim, for example, focus on "Hansel and Gretel" as a story about the "destructive desires," "uncontrolled cravings," and "ambivalent feelings" of the protagonists rather than as a story about adult hostility toward children. After examining how fairy tales were converted into children's literature, the author investigates the acculturation of heroines in such stories as "Cinderella" and "Beauty and the Beast" and concludes with meditations on violence, cannibalism, and conflicts between parents and children. Since the cultural stories we read to children in their "formative years" have a powerful influence on their lives, Tatar emphasizes the importance of interrogating and reinterpreting these bedtime tales.